Longitudinal Structural Brain Changes in Bipolar Disorder: A Multicenter Neuroimaging Study of 1232 Individuals by the ENIGMA Bipolar Disorder Working Group - Abé, Christoph; Ching, Christopher R K; Liberg, Benny; Lebedev, Alexander V; Agartz, Ingrid; Akudjedu, Theophilus N; Alda, Martin; Alnæs, Dag; Alonso-Lana, Silvia; Benedetti, Francesco; Berk, Michael; Bøen, Erlend; et al. (Biological psychiatry, 2022)
BACKGROUND: Bipolar disorder (BD) is associated with cortical and subcortical structural brain abnormalities. It is unclear whether such alterations progressively change over time, and how this is related to the number of mood episodes. To address this question, we analyzed a large and diverse international sample with longitudinal magnetic resonance imaging (MRI) and clinical data to examine structural brain changes over time in BD. METHODS: Longitudinal structural MRI and clinical data from the ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) BD Working Group, including 307 patients with BD and 925 healthy control subjects, were collected from 14 sites worldwide. Male and female participants, aged 40 ± 17 years, underwent MRI at 2 time points. Cortical thickness, surface area, and subcortical volumes were estimated using FreeSurfer. Annualized change rates for each imaging phenotype were compared between patients with BD and healthy control subjects. Within patients, we related brain change rates to the number of mood episodes between time points and tested for effects of demographic and clinical variables. RESULTS: Compared with healthy control subjects, patients with BD showed faster enlargement of ventricular volumes and slower thinning of the fusiform and parahippocampal cortex (0.18 <d < 0.22). More (hypo)manic episodes were associated with faster cortical thinning, primarily in the prefrontal cortex. CONCLUSIONS: In the hitherto largest longitudinal MRI study on BD, we did not detect accelerated cortical thinning but noted faster ventricular enlargements in BD. However, abnormal frontocortical thinning was observed in association with frequent manic episodes. Our study yields insights into disease progression in BD and highlights the importance of mania prevention in BD treatment.
Keywords: ENIGMA; multicentrické studie jako téma; Neuroprogression; Neuroimaging; Multicenter Studies as Topic; Mania; bipolární porucha; Middle Aged; mužské pohlaví; Psychiatry; Bipolar disorder; mozek; Adult; mladý dospělý; mánie; Bipolar Disorder; magnetická rezonanční tomografie; ztenčování mozkové kůry; Magnetic Resonance Imaging; Brain; Young Adult; Longitudinal study; ženské pohlaví; Humans; neurozobrazování; lidé středního věku; dospělí; Cerebral Cortical Thinning; Female; lidé; Male